PENINGKATAN HASIL BELAJAR BAHASA INGGRIS MELALUI APLIKASI DUOLINGO DALAM PEMBELAJARAN ONLINE DI TENGAH COVID-19 PADA SISWA SMP KATOLIK DELIMURNI DELITUA - Purba, Nancy Angelia; Saragih, Marice (Unversitas Katolik Santo Thomas, 2022)
Duolingo aplication is one media that very useful in learning, especially in learning English. This is because this application can improve the students’ skilss in English. The application can be used repeatedly and continuously until the students understand about the material. The purpose of this research was to improve students learning outcomes in English in class VII of Junior High School Students and to make the students interest in studying Englsih.The sample used in this study was consist 61 students. The method used in this study is quantitative research methhod, this study has two variables : the Variable (X) is duolinggo Aplication and the Variable (Y) is the improvement of English learning outcomes. The instrument in collecting data is a sheet of students test result in the control group and experimental group. From the result of this study indicate that pre-test and post-test in the control group and experimental group it can be concluded that duolingo aplplication can : ( 1) Improve students learning outcomes or students learning achievement in SMP Katolik class VII Delimurni (2) Increase the interest of students of class VII SMP Katolik Delimurni in learning English, as evidenced by the significant increase in the result of the students score betweeen control group and experimental group. The result of the students average score in the pre-test in the control group was 47,26 and the post test 55.00, the averange score in the experimental group in the pre-test was 51,67 and the post test was 79,26. Therefore it can say that the use of duolingo application can enhance learning outcomes and students’ speaking ability in English